Effects of Chitosan and Silver Nanoparticles on Germination and Early Seedling Growth of Pea (Pisum sativum L.) - Laila Mohamed Gebril; Abusif Sonousi; Bilkess Meloud Salim (Journal of Scientific and Human Dimensions, 2026)
Seed priming is an important pre-sowing technique that enhances seed germination, seedling growth, and crop establishment. The current study was carried out during the 2025-2026 growing season in the Crops Laboratory, Department of Crops, Faculty of Agriculture, Sebha University, Libya to test the seed priming effects of distilled water (hydro-priming), various concentrations of chitosan (0.5%, 1%, and 3%) and silver nanoparticles (AgNPs) (5, 10, and 20 ppm) on the germination, Seeds were soaked in distilled water (control) or treatment solutions for 3 hours. The findings revealed that the chitosan and the AgNPs influenced the germination and seedling growth parameters as compared to the control. The optimum chitosan concentration was 0.5 % with better germination percentage (96.9 %), germination index (10.00) and root length (10.4 cm) and when concentration was increased to 3 %, most of the growth characteristics were reduced especially shoot length (4.8 cm). Conversely, AgNPs showed a concentration-dependent response, with 20 ppm showing the best performance in germination and some growth parameters. In addition, certain seedling growth phenotypes such as shoot length (6.53 cm) and fresh weight (1.042 g) but others were not consistently different from the control. Overall, chitosan worked better at low concentrations, and AgNPs worked better at medium to high concentrations. These results indicate the need to maximize priming levels to promote seed germination and early seedling development of pea.